Gambaran Pengetahuan Kader dan Orang Tua tentang Deteksi Dini Stunting - Hidayati, Bq. Nurul; Eka Adithia Pratiwi; Nopiyanti, Ni Made Ari (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Stunting, a chronic condition of malnutrition in children under five, can have a serious impact on their quality of life. Limited knowledge among posyandu cadres, who play an important role in growth monitoring and nutrition counseling, may result in misinterpretation of nutritional status and inaccurate information to parents. This study aimed to assess the understanding of posyandu cadres and parents regarding early identification of stunting. This descriptive cross-sectional study involved 166 participants (70 cadres and 96 parents) selected through cluster random sampling. Data were collected using a questionnaire that had been tested for validity and reliability. The results showed that most cadres (61.4%) and parents (79.2%) had good knowledge about early detection of stunting. Only a small proportion of both groups had poor knowledge (1.4% of cadres and 1.0% of parents). In conclusion, both cadres and parents generally have a good knowledge level about early stunting detection. However, it is recommended that cadres receive additional training to improve their ability to conduct early detection and provide more accurate information to parents